Over the roofs of the world - Senior, Olive (Insomniac Press, 2005)
Using nature as both model and metaphor, Toronto resident Olive Senior delves into birds, flying, and Caribbean life in her third book of poems. Following her much-loved collections, Gardening in the Tropics and Talking of Trees, this long-awaited book of poems is sure to delight readers around the world. Translated into several languages, represented in numerous anthologies, and broadcast in Canada, Britain, and the Caribbean, Senior's work enjoys international acclaim. Her work is taught at universities around the world, and her short story collection, Summer Lightning, has been a literature.